Sexual selection of male parental care in giant water bugs. Issue 5 (May 2016) - Ohba, Shin-ya; Okuda, Noboru; Kudo, Shin-ichi
Abstract : Paternal care can be maintained under sexual selection, if it helps in attracting more mates. We tested the hypothesis in two giant water bug species, Appasus major and Appasus japonicus, that male parental care is sexually selected through female preference for caring males. Females were given an opportunity to choose between two males. In the first test of female mate choice, one male carried eggs on its back, while the other did not. The egg status was switched between these two males in the second test. The experiment revealed that females of both species preferred caring males (i.e. egg-bearing) to non-caring males. Nonetheless, the female mate preference for egg-bearing males was stronger in A. major than in A. japonicus . Our results suggest that sexual selection plays an important role in maintaining elaborate paternal care in giant water bugs, but the importance of egg-bearing by males in female mate choice varies among species.